Gaussian Layer Connectivity Parameterization: A New Approach to Topology Optimization of Multi-Body Mechanisms. (October 2019) - Swartz, Kenneth E.; James, Kai A.
Abstract: Topology optimization is extended to the design of multi-body mechanisms. A Gaussian function is used to parameterize the location of inter-body connections, thereby enabling the optimization of both mass distribution and inter-body connectivity simultaneously. The potential for large rigid-body rotation necessitates the use of a geometrically nonlinear finite element analysis to properly model mechanism response. The unknown displacement field is calculated with a Newton–Raphson iterative scheme. An adjoint analysis is performed to efficiently compute the design sensitivities used in the gradient-based optimization procedure. The proposed technique is demonstrated on the design of multi-body grippers and force/displacement inverters. Highlights: We propose a topology optimization method for design of multi-body mechanisms. We introduce a novel Gaussian formulation to parameterize the inter-body connectivity. The mechanisms are modeled using geometrically nonlinear finite elements analysis. We implement adjoint sensitivity analysis to guide the gradient-based optimization. We present results for several example problems including multi-body gripper design.